Model pembelajaran empati untuk membangun sekolah berwawasan multikultural - Bambang Kariyawan Ys (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2020)
The purpose of this study is to look at the steps of implementing empathy learning models that can build multicultural schools with insight. The method of research this is literature review with techniques to collect the data from a variety of sources written in the form of books, journals, articles science or literature review. The results of the research it is in the form of design models and the stages of implementation of the model of learning empathy that do teachers and outside the classroom in the form of an attitude accept differences in background behind the social culture of a person. Measurement of learning outcomes of empathy learning models is measured by authentic assessment in the form of observing attitudes and the process of interacting in groups, case studies, performance and portfolio.